2017
DOI: 10.17113/ftb.55.03.17.5040
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hypoallergenic Antibacterial Peptides from Defatted Soybean Meal by a Membrane Associated Bioreactor: A Bioprocess Engineering Study with Comprehensive Product Characterization

Abstract: SummaryHypoallergenic antibacterial low-molecular-mass peptides were produced from defatted soybean meal in a membrane bioreactor. In the fi rst step, soybean meal proteins were digested with trypsin in the bioreactor, operated in batch mode. For the tryptic digestion of soybean meal protein, optimum initial soybean meal concentration of 75 g/L, temperature of 40 °C and pH=9.0 were determined. Aft er enzymatic digestion, low-molecular-mass peptides were purifi ed with cross-fl ow fl at sheet membrane (pore siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Cumulative number of peptides, produced in batch-mode enzymatic hydrolysis reaction, offered a comparatively high zone of inhibition. In another investigation, we found that peptides with molecular weight lower than 5 kDa, produced by tryptic hydrolysis of defatted soybean meal protein, had antibacterial activity against Gram-positive B. cereus [8]. However, sources of peptides were different, i.e., soybean milk and defatted soybean meal, and they were prepared by enzymatic hydrolysis with papain and trypsin, respectively; their antimicrobial activity on test microorganism were similar.…”
Section: Antibacterial Activitymentioning
confidence: 98%
See 3 more Smart Citations
“…Cumulative number of peptides, produced in batch-mode enzymatic hydrolysis reaction, offered a comparatively high zone of inhibition. In another investigation, we found that peptides with molecular weight lower than 5 kDa, produced by tryptic hydrolysis of defatted soybean meal protein, had antibacterial activity against Gram-positive B. cereus [8]. However, sources of peptides were different, i.e., soybean milk and defatted soybean meal, and they were prepared by enzymatic hydrolysis with papain and trypsin, respectively; their antimicrobial activity on test microorganism were similar.…”
Section: Antibacterial Activitymentioning
confidence: 98%
“…After the experiment, ultrafiltration membrane was cleaned thoroughly with sequential way, as mentioned: (a) Cleaning with 10 g/L of ultrasil P3-11 for 30 min, (b) cleaning with deionized water for 30 min, (c) cleaning with 10 g/L of citric acid for 30 min, and (d) cleaning with deionized water for 1 h. Retentate flow rate of 200 L/h and trans-membrane pressure of 0.8 bar were used during the cleaning with ultrasil and citric acid, whereas trans-membrane pressure of 5 bar and retentate flow rate of 200 L/h were used during the cleaning with water [8]. Membrane hydraulic resistance (R m ) was estimated prior to the experiment, after the experiment, and membrane cleaning.…”
Section: Membrane Cleaningmentioning
confidence: 99%
See 2 more Smart Citations
“…As the byproduct of oil processing industry, soybean meal has high protein content and is an excellent raw protein material (Zheng et al, 2017;Rumsey et al, 1994;Mukherjee et al, 2016). However, soybean meal is currently mainly used as feed, with only a small part of it employed in fermentation and the majority of the protein material not being effectively utilized, resulting in wastage of resources (Lawrence et al, 2003;Ortega et al, 2016;Nath et al, 2017). Thus, the use of soybean meal as a raw material for further processing and comprehensive utilization has significant prospects (Wang et al, 2017;Liu et al, 2017;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%